Carta de "Headquarters Department of Porto Rico, Civil Division, San Juan" a Roberto H. Todd - Todd, Roberto H.; Headquarters Department of Porto Rico, Civil Division, San Juan (My University, 1899)
Carta relacionada sobre la aprobación del pedido para transportar a estudiantes de Puerto Rico a Estados Unidos.
Keywords: The Cuban Educational Association; Education--Puerto Rico.; Educación--Puerto Rico.